2014
DOI: 10.1007/s00192-014-2517-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of adding pelvic floor muscle training to bladder training for female urinary incontinence: a randomized controlled trial

Abstract: High-intensity PFMT combined with BT is more effective than BT alone in the short term for treating UI or SUI. It appears that the combination therapy may also lead to greater benefits for patients with UUI and MUI. Based on the results of this study, further studies with larger sample sizes (for UUI) and long-term follow-ups are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 13 publications
0
43
3
2
Order By: Relevance
“…In a recent randomized trial of 108 women in Turkey, 6 weeks treatment of BT with PFMT versus BT alone [26], the results showed that more patients in the former group reported cured or improved symptoms (100 vs. 82.7%, p  = 0.038). Combined therapy also showed reduction in micturition frequency and leak accidents in stress urinary incontinence patients but there were no difference for patients with urgency and mixed urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent randomized trial of 108 women in Turkey, 6 weeks treatment of BT with PFMT versus BT alone [26], the results showed that more patients in the former group reported cured or improved symptoms (100 vs. 82.7%, p  = 0.038). Combined therapy also showed reduction in micturition frequency and leak accidents in stress urinary incontinence patients but there were no difference for patients with urgency and mixed urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…The BT has varied definitions and it has been used as behavioral therapy including PFMT [25]. In our study, BT was assigned as arm A and PFMT as arm B similar to Kaya et al [26]. There are many studies where efficacy of BT including PFMT for OAB treatment has been compared with pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral therapy includes the association of various resources, such as: educational program; changes in lifestyle; bladder training and urge suppression strategies; pelvic floor muscle training (PFMT); electro-stimulation; and programmed urination. [6][7][8] The effects of behavioral therapy in the treatment of OAB symptoms are extensively studied and their efficacy, proven. 9 The literature investigating the effects of PFMT on OAB symptoms, without the association of other techniques, is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…However, no significant improvement in UI was noted at 4 weeks, and we assumed that the absence of improvement in UI after 4 weeks of PFME may have been associated with the characteristics of the patients that influenced the severity of UI. A previous study reported that 6 weeks of PFME combined with BT led to a significant improvement in UI [ 20 ]. They observed improvements in UI after a short-term treatment, but we did not observe a significant decrease in the number of UI episodes at 4 weeks.…”
Section: Discussionmentioning
confidence: 99%